Application of information technology in the southeast macroregion agribusiness of the state of Mato Grosso (Research, Society and Development, 2021)
This work has as main objective to measure the degree of technology used in the management of the field, through a quantitative sampling on management of processes in the agribusiness, with the application of information technologies and softwares based on ERP, focusing on the macro-region southeast of Mato Thick. The survey was conducted via email and telephone, with 15.19% of producers in the universe surveyed and has a 95% reliability level. An overview of ERP software is presented, as well as some technologies most used in the field, exemplifying their use and a brief history of how they emerged and how their users benefit today. Through the research it was possible to determine which are the most used software, which are the internal sectors controlled by ERPs, in addition to the degree of connectivity that the investigated real properties have. With the data obtained, it was also possible to know how producers who have not yet adhered to the use of ERPs manage their properties and why they have not yet chosen to migrate to more efficient management systems.